ANALISIS POLA DAYA TARIK WISATA BERDASARKAN POTENSI SUMBERDAYA (SUPPLY) SEBAGAI ASET DAN DAYA TARIK DI DAERAH ISTIMEWA YOGYAKARTA - Wahyuni, Sri (Kepariwisataan: Jurnal Ilmiah, 2020)
The purpose of this research is to study and to analyze the pattern of tourist destinations to determine the excellence of attractions in each district in the Special Region of Yogyakarta, as a tourist attraction. This research uses qualitative research methods with sampling techniques using positive sampling. Data sources used are informants, tourist attractions, and documents. Determination of the advantages of a tourist attraction in a regency and even in the Special Region of Yogyakarta aims to increase the selling power or visitors of a tourist attraction and become an icon or mascot in the regency or region in Yogyakarta Special Region. From the results of the discussion, it was concluded that the most preeminent in the Yogyakarta Special Region was Tourism, Beach and Temple Villages. Keywords: Tourist Patterns, Tourist Attraction, Tourist Asset, Potential Resources